STRATEGI PEMASARAN DALAM MEMPERTAHANKAN BISNIS DI TOKO SYARAH BAKERY KOTA BENGKULU - Eti PERMATA Arini; DIA PERMATA SARI (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
The purpose of this study is 1) knowing how the Syarah Bakery Kota Bengkulu store carries out Product Innovation; 2) knowing how the Syarah Bakery Kota Bengkulu store sets competitive prices and according to quality; 3) knowing that the Syarah Bakery Kota Bengkulu store is promoting; 4) knowing how the Syarah Bakery store maximizes the place. Data collection techniques with observation, interviews, and documentation. Data analysis techniques use data reduction, data exposure and drawing conclusions. The results of this study show that the business marketing strategy of Syarah Bakery Kota Bengkulu in maintaining its business through the Strengths-Opportunities (SO) Strategy, namely 1) Maintaining Product Quality, the quality of a product determines a business so that it continues to run and develop. Maka dari itu kualitas dan mutu produk yang ada di Syarah Bakery Kota Bengkulu harus tetap dijaga agar terus diminati konsumen dan mampu bersaing dengan usaha sejenis. 2) Menambah variasi produk, Masyarakat Kota Bengkulu merupakan masyarakat yang heterogen baik dalam strata sosial, ekonomi, suku, usia. Therefore, Syarah Bakery should vary the shape and size and taste of the product so that it can meet the needs of tastes and be affordable for all people. 3) Increasing pomosi, In the current technological era. Keywords : Marketing Mix, Business Sustaining Strategy